A case report: mechanical tricuspid valve thrombosis necessitating cardiac surgery during pregnancy - Sathananthan, Gnalini (Eur Heart J Case Rep, 2019)
BACKGROUND: Pregnant women with mechanical valves are considered a high-risk pregnancy. They carry an increased risk of both maternal and foetal complications. This includes maternal valve thrombosis, foetal embryopathy, and haemorrhage. Cardiac surgery is generally avoided during pregnancy, and is used when there are no other alternative options. Cardiopulmonary bypass (CPB) during pregnancy is associated with high foetal mortality. Maternal mortality in the setting of CPB however, is not dissimilar to a non-pregnant woman. CASE SUMMARY: We present the case of a 29-year-old woman with Ebstein’s anomaly who developed thrombosis of her mechanical tricuspid valve at 4 weeks’ gestation. This was suspected to be likely due to sub-therapeutic anticoagulation at the time of presentation. She underwent a tricuspid valve replacement during the first trimester of pregnancy after failing medical therapy, with overall favourable maternal and foetal outcomes. DISCUSSION: Valve thrombosis during pregnancy is a devastating complication. There is limited data surrounding the best management strategy of valve thrombosis in pregnancy. Cardiac surgery with CPB is reserved for cases refractory to appropriate medical therapy. Though maternal mortality is largely unaffected, foetal mortality with CPB remains high. The management of pregnant women undergoing CPB is unique and extremely challenging. It requires a meticulous, multidisciplinary approach to improve overall outcomes.